Moral Education Strategies for Islamic Boarding School Students Through a Community-Based Approach: A Case Study at Al-Hidayah Islamic Boarding School, Tenggarong - Muhammad Ikhsan; Nur Emilia; Windi; Ana Setiyani Mutia Mutia; Muhammad Hastiavin Habibi; Mubarok (STAI Yogyakarta, 2026)
This study aims to analyze strategies for moral education for students through a community-based approach at the Al-Hidayah Islamic Boarding School in Tenggarong. The study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the boarding school leadership, male teachers (ustadz), female teachers (ustazah), and students. The results indicate that character education is implemented through the exemplary conduct of teachers, daily routines, regular mentoring activities, the provision of advice, character evaluations every semester, supervision, and special guidance for students requiring additional attention. The boarding school environment, as a community, exerts a significant influence on shaping students’ character through a culture of discipline, courtesy, responsibility, and religious devotion. The primary challenges faced include variations in students’ personalities and the time-consuming nature of the moral transformation process. Additionally, students’ family backgrounds and pre-boarding school habits pose further challenges in the moral development process. However, through collaboration between boarding school leaders, ustadz, ustazah, and fellow students, the moral education process can proceed more effectively and sustainably. Intensive social interaction within boarding school life further strengthens the internalization of moral and religious values in students. This study demonstrates that a community-based approach is effective in supporting the sustainable and relevant development of students’ moral character.